2018
DOI: 10.1186/s12919-018-0143-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene-methylation epistatic analyses via the W-test identifies enriched signals of neuronal genes in patients undergoing lipid-control treatment

Abstract: An increasing number of studies are focused on the epigenetic regulation of DNA to affect gene expression without modifications to the DNA sequence. Methylation plays an important role in shaping disease traits; however, previous studies were mainly experiment, based, resulting in few reports that measured gene–methylation interaction effects via statistical means. In this study, we applied the data set adaptive W-test to measure gene–methylation interactions. Performance was evaluated by the ability to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This application was originally reported in Sun et al 2018 [3]. The data set contains 476 diabetic patients undergone lipid control treatments, and 150,000 candidate SNP-CpG pairs within 10kb genome distance ( w i n d o w .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This application was originally reported in Sun et al 2018 [3]. The data set contains 476 diabetic patients undergone lipid control treatments, and 150,000 candidate SNP-CpG pairs within 10kb genome distance ( w i n d o w .…”
Section: Resultsmentioning
confidence: 99%
“…s i z e =10,000). The phenotype is whether or not a subject responded to the treatment, calculated by comparing the before and after treatment triglyceride levels [3]. The h and f are estimated by hf.snps.meth() , and the gene-methylation interactions are calculated by wtest.snps.meth() .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all brain regions studied, the levels of NAV2 observed in late gestation and early postnatal life were the highest [27]. It was reported that NAV2 was associated with hyperlipidemia [29]. The glycoprotein MUC15 was initially isolated from the bovine milk fat globule membrane, and had potential physiological function in signal transduction [30].…”
Section: Discussionmentioning
confidence: 97%
“…Studies reported that MTHFR was an important candidate gene for sheep milk yield traits ( Hou et al, 2015 ; An et al, 2016 ). NPPB and BTNL2 were involved in PI3K/AKT, Ca 2+ , K + , ATP, and immunity ( Fioretti et al, 2004 ; Dolovcak et al, 2009 ; Sun et al, 2018b ; Zhao et al, 2020 ). KIAA2013 was related to DNA methylation levels of newborns ( Yeung et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%